Pengaruh Environmental, Social, And Governance (ESG) Pada Profitabilitas Perusahaan Sub Sektor Food & Beverage Yang Terdaftar Di BEI 2021-2023 - Siti Syawaliah; Rusdayanti Asma; Redawati Redawati; Akhmad Supriyanto (CV. Anugerah Duta Perdana, 2026)
This study empirically tests and proves the influence of environmental, social, and governance (ESG) on the profitability of companies in the food & beverage sub-sector listed on the IDX from 2021 to 2023. The independent variables in this study use Environmental, Social, and Governance. Company profitability as a dependent variable is measured by Return On Assets (ROA). Using a quantitative method, the study employs secondary data obtained from companies' annual financial reports and sustainability reports. The sample was selected using purposive sampling to determine the sample size, resulting in 10 companies from a population of 95 companies. Data analysis was conducted using SPSS software, including descriptive analysis, classical assumption tests, F-tests, t-tests, and R² tests. The results of the study indicate that environmental factors have a significant negative impact on company profitability, social factors have a significant positive impact on company profitability, while governance factors have a significant negative impact on company profitability